Suspicion of neglect or abuse in two hospitalized cases (Case report) - Moersintowarti B. Narendra; Hardjono Soeparto; Yustina Rosanti; Agus Salim (Indonesian Pediatric Society Publishing House, 2001)
The convention of children's rights (1989) has acknowledged and recommended a statement that minimal standard for the child welfare with the range of primary right to keep an outstanding life for the children's development to their maximum potential, protecting from disturbances e.g. neglect and physical abuse.But, it is difficult to classify cases whether related to the problem of neglect or abuse, especially in developing countries where discrepancies in health services is remain exist.Objective : To present two cases which have been overlooked to the possibilities of abuse and neglect. Discription of the cases :Case 1. A malnourished 2 years old boy who was admitted with diarrhea in Dr.Soetomo Hospital Surabaya (September 6 ,1998) with :Clinical criteria of Marasmic Kwashiorkor available.Ignorance of health worker about nutritional status and inadequate referral system. 3. Factors related to the malnutrition are: a. Early weaning and inadequate weaning food. b. Poverty and low education. c. Lack of integrated health care (GOBI FFF practice). Case 2. An epileptic 11 years old girl was admitted in Dr.Soetomo Hospital Surabaya (July,12, 1999). Problems list were : Respiratory problem which could not be explained pathophysiologically. Single parent, and inconsistency of adequate childrearing , Factors related to the failure in compliance of epileptic treatment, and Isolation and restricted movement.Discussion of the difficulty in classification of the cases, and the possibility of solving the problem in Surabaya related to the limited action of the Committee on Child Protection, need to have positive suggestions sharing experience from the Congress members.